Best Practices in Distance Education Program Selection - Anderson, Dawn (Annual Conference on Distance Teaching and Learning, 2009)
How are academic programs selected for electronic delivery? What are the next hot areas for e-learning programming? Public higher education institutions are being urged to help develop a knowledgeable, skilled and creative workforce that will drive sustained economic growth and diversification. They are being asked to address specific workforce needs while continuing to provide academic excellence in traditional curricular areas. New e-learning programs are frequently self-funded and therefore, must be viewed as a business decision with inherent financial risks. E-learning program selection strategies and processes were researched. Considerations included: institutional strategic plans or policy statements guiding e-learning programming; program selection criteria; and, decision-making tools. Case studies were used to evaluate strategies for identifying and selecting new e-learning programs.
Keywords: Institute for Academic Alliances; Distance Education; Online Education; Higher Education Administration; Distance Education Programs